2022
DOI: 10.3389/fmicb.2022.963678
|View full text |Cite
|
Sign up to set email alerts
|

The response of cecal microbiota to inflammatory state induced by Salmonella enterica serovar Enteritidis

Abstract: By combining the experiments of reciprocal crosses of chicken infected with Salmonella enterica serovar Enteritidis (S. Enteritidis), we focused on the common response of cecal microbiota to an inflammatory state in respect of transcriptome and microbiome. The inoculation of S. Enteritidis improved the microbial diversity and promoted the microbiota evolution in our infection model. Correlation analysis between bacteria and inflammation-related genes showed that some intestinal microorganisms were “inflammophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…As described in our previous study (Hu, Liu, Miao, Zhao, Peng, et al, 2022), the result of 16S rRNA gene | 91 sequencing showed that S. Enteritidis was detected in a mean abundance of 1.09% (from 0.01% to 4.27%) in Salmonella groups (CT and RT) but not in control groups (CC and RC), suggesting S. Enteritidis can colonize in the cecal contents of chickens. We did not measure the colony-forming units of other organs.…”
Section: The Phenotypic Discrepancy In Metabolome Between the Recipro...supporting
confidence: 63%
See 3 more Smart Citations
“…As described in our previous study (Hu, Liu, Miao, Zhao, Peng, et al, 2022), the result of 16S rRNA gene | 91 sequencing showed that S. Enteritidis was detected in a mean abundance of 1.09% (from 0.01% to 4.27%) in Salmonella groups (CT and RT) but not in control groups (CC and RC), suggesting S. Enteritidis can colonize in the cecal contents of chickens. We did not measure the colony-forming units of other organs.…”
Section: The Phenotypic Discrepancy In Metabolome Between the Recipro...supporting
confidence: 63%
“…It was reported that chicken genotype has a limited effect on resistance to S. Enteritidis infection between two inbred lines (Mon et al, 2015). Compared to the two regional chickens, their reciprocal crosses will be less influenced by genetic background and help us to find out the common response across hybrids, which had been reflected in our new studies (Hu, Liu, Miao, Zhao, & Li, 2022;Hu, Liu, Miao, Zhao, Peng, et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this study, we also detected that the extracellular fatty acid binding protein (EXFABP) was significantly downregulated at 21 dpi compared to 7 dpi in chickens with low H/L ratio. In their study, Hu et al demonstrated that Salmonella Enteritidis (OTU607) was positively correlated with EXFABP among others genes, indicating that Salmonella Enteritidis infection arouses EXFABP transcription in chicken, which induces the sequestration of siderophore secreted by enteric bacteria and Gram-positive bacilli, such as Escherichia-Shigella and Enterococcus, resulting in a decrease of their abundance [50]. During infection, Salmonella escapes the antibacterial effect of EXFABP-mediated growth inhibition through salmochelin, which is not recognized by EXFABP [50].…”
Section: Discussionmentioning
confidence: 99%